Severe Convection Features in the Amazon Basin: A TRMM-Based 15-Year Evaluation - Nunes, Ana M. P.; Silva Dias, Maria A. F.; Anselmo, Evandro M.; Morales, Carlos A. (Frontiers in Earth Science, 2016)
Rainfall in the Amazon Basin is very heterogeneous, mainly because the area encompassed is quite large. Among the systems responsible for rainfall, some stand out as extreme storm events. This study presents a criterion for identifying potentially severe convection in the Amazon region from the Tropical Rainfall Measuring Mission (TRMM) database, specifically from Precipitation Features (PF) - 1998-2012 - generated and stored by the University of Utah. The seasonal and spatial distributions are similar to distributions of Mesoscale Convective Systems already catalogued in previous studies based on GOES satellite images. The seasons with the highest number of cases are austral spring, winter, and fall. With the Amazon region divided into six subregions and cases accumulated by quarter (JFM, AMJ, JAS, OND) the south of the Amazon subregion (SA) accounts for the largest number of cases with the OND quarter with higher occurrence and the lowest in AMJ. Different diurnal cycles of potentially severe convection are observed across the region with the more western areas, closer to the Andes, favoring nighttime cases, especially in the austral spring and summer. The diurnal cycle of the number of the most extreme cases is more pronounced than the diurnal cycle when a large collection of deep convection cases are included.